(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article examines the sociolinguistic impact of Global English on local languages, focusing on language shift, hybridization, and cultural identity. The widespread adoption of English as a global lingua franca has facilitated international communication and economic growth but has also contributed to linguistic endangerment and cultural homogenization. This study explores the consequences of English dominance on linguistic diversity, the role of language policies in mitigating negative effects, and potential strategies for balancing global communication with the preservation of local languages.